Pengaruh Kepercayaan dan Persepsi Resiko terhadap Keputusan Pembelian Aset Digital Cryptocurrency Dikalangan Masyarakat Kecamatan Tapos - Anzar Lazuardi; Dedy Syahyuni (UNIVERSITAS MARITIM AMNI SEMARANG, 2025)
This study aims to analyze the influence of trust and risk perception on cryptocurrency purchase decisions in Tapos District. The research uses a descriptive quantitative method, with primary data collected through online and direct questionnaires. The sample consists of 122 respondents selected using the Slovin formula from a population of 177 people. Data were analyzed using SPSS 25 with multiple linear regression techniques. The results show that both trust and risk perception partially have a significant influence on cryptocurrency purchase decisions. Simultaneously, trust and risk perception also significantly affect purchase decisions. These findings indicate that trust in platforms and perceived risk levels are critical factors influencing cryptocurrency purchase decisions among the Tapos District community.